The Effect Of Work Culture And Human Rights-Based Public Services On Visitor Satisfaction In The Class IIA Muara Padang Correctional Institution - KHAIRUN NISA; Aldri Frinaldi (Jurnal Teori dan Riset Administrasi Publik, 2020)
Factors that can affect visitor satisfaction are human rights-based work culture and public services. In this study, the author aims to identify and explain the Influence of Work Culture and Human Rights-Based Public Services on Visitor Satisfaction at Muara Padang Class IIA Correctional Institution. This research uses associative quantitative method. The sampling technique in this study using accidental sampling technique. The accidental sampling technique is a technique of determining the sample based on chance. The sample in this study amounted to 100 visitors or visitors who were visiting the Class IIA Muara Padang Correctional Institution. The data collection tool in this study was a questionnaire using a Likert scale measurement. The analysis of this research uses multiple linear regression analysis. The results showed that there was a significant influence between work culture on visitor satisfaction with an R Adjusted Square value of 0.144. Furthermore, in the human rights-based public service variable on visitor satisfaction there is also a significant influence with the R Adjusted Square value of 0.226 and there is a simultaneous significant influence between work culture and human rights-based public services on visitor satisfaction seen from the regression test results. Adjusted R Square value of 0.267. It can be said that there is an influence partially or simultaneously in this study.